2007
DOI: 10.1038/sj.leu.2404833
|View full text |Cite
|
Sign up to set email alerts
|

Tissue repair using allogeneic mesenchymal stem cells for hemorrhagic cystitis, pneumomediastinum and perforated colon

Abstract: Mesenchymal stem cells (MSC) possess anti-inflammatory properties and participate in tissue repair. We used MSC to heal therapy-induced tissue toxicity. Ten consecutive patients, treated with MSC due to tissue toxicity following allogeneic hematopoietic stem cell transplantation, (ASCT) were included. Their median age was 48 (13-64) years. Seven had hemorrhagic cystitis grades 2-5, two had pneumomediastinum and one had perforated colon and peritonitis. MSC donors were mainly third-party, HLA-mismatched (n=11),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
153
2
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(166 citation statements)
references
References 32 publications
4
153
2
7
Order By: Relevance
“…The patient's disturbed hemostasis and systemic vasodilatation may not only have caused the extensive microembolization and macroembolization observed in the lungs but may also explain the wide distribution of the MSCs. In one patient (1033), the extrapulmonary finding of MSC donor DNA correlated with the known intestine and bladder sites of injury, but no general tendency of homing to damaged tissue was found in this material [15].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The patient's disturbed hemostasis and systemic vasodilatation may not only have caused the extensive microembolization and macroembolization observed in the lungs but may also explain the wide distribution of the MSCs. In one patient (1033), the extrapulmonary finding of MSC donor DNA correlated with the known intestine and bladder sites of injury, but no general tendency of homing to damaged tissue was found in this material [15].…”
Section: Discussionmentioning
confidence: 74%
“…The first method, a nested PCR described previously [15], is nonquantitative and was used in three patients (917, 924, and 1033). Primers were designed based on differences in the HLA type between the MSC donors, the patients, and the HSCT donors.…”
Section: Methodsmentioning
confidence: 99%
“…101 Stromal cells have a profound effect on coagulation, 18,20 which partly explains their effectiveness in stopping major hemorrhages. 90,102,103 BM must be accessed by aspiration, and this source of MSCs has been challenged by MSCs from adipose tissue, umbilical-cordderived MSCs and stromal cells from the placenta-such as DSCs. Placental stromal cells are accessible without any invasive procedure and with little ethical consideration.…”
Section: Discussionmentioning
confidence: 99%
“…With the support of MSCs successful results were obtained for patients with hemorrhagic cystitis whose treatment are complicated by colon perforation [9]. Some health centers think that MSCs may prove insufficient to avoid toxicity mediated by cytotoxic T cells, therefore it has been suggested that MSCs must be combined with systemic immunosuppressive therapy to provide adequate T cell suppression [14].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can help improve tissue toxicity associated with allo-HSCT, by repairing the damaged tissue. MSCs also promise good results for the treatment of GVHD associated with HSCT [9,10].…”
Section: Case Reportmentioning
confidence: 99%